2018
DOI: 10.1186/s12870-018-1413-3
|View full text |Cite
|
Sign up to set email alerts
|

Low pH-responsive proteins revealed by a 2-DE based MS approach and related physiological responses in Citrus leaves

Abstract: BackgroundRare data are available on the molecular responses of higher plants to low pH. Seedlings of ‘Sour pummelo’ (Citrus grandis) and ‘Xuegan’ (Citrus sinensis) were treated daily with nutrient solution at a pH of 2.5, 3, or 6 (control) for nine months. Thereafter, we first used 2-dimensional electrophoresis (2-DE) to investigate low pH-responsive proteins in Citrus leaves. Meanwhile, we examined low pH-effects on leaf gas exchange, carbohydrates, ascorbate, dehydroascorbate and malondialdehyde. The object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…At least two of matched peptides were necessary for each protein. Protein identifications were accepted if MASCOT score was ≥ 70, and the sequence coverage was ≥ 20% or the number of matched peptides (NMP) was ≥ five [84,85]. DAPs were classified according to KEGG (http://www.kegg.jp/), GO (http://www.geneontology.org/) and Uniprot (http://www.uniprot.org/) databases [86,87].…”
Section: Maldi-tof/tof-ms-based Protein Identification and Bioinformamentioning
confidence: 99%
“…At least two of matched peptides were necessary for each protein. Protein identifications were accepted if MASCOT score was ≥ 70, and the sequence coverage was ≥ 20% or the number of matched peptides (NMP) was ≥ five [84,85]. DAPs were classified according to KEGG (http://www.kegg.jp/), GO (http://www.geneontology.org/) and Uniprot (http://www.uniprot.org/) databases [86,87].…”
Section: Maldi-tof/tof-ms-based Protein Identification and Bioinformamentioning
confidence: 99%
“…Considerable research has been performed to clarify the mechanisms of Al-toxicity and -tolerance in plants [511]. Nevertheless, limited data are available on the responses of plants to low pH [1214]. Although some plants grow well in acidic soils with high level of active Al, the adaptive mechanisms of plants to low pH and Al-toxicity are not exactly the same [3, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, soil acidity is becoming an increasing urgent problem in some Citrus orchards [22]. Although the physiological and molecular responses of Citrus to Al-toxicity or low pH have been investigated in some details [9, 2325], very scarcity is known on Citrus responses to pH and Al interactions. Preliminary study showed that increasing nutrient solution pH prevented Al-toxic effects on Citrus growth and photosynthesis.…”
Section: Introductionmentioning
confidence: 99%